Healthy lunch box program on eating habits and nutritional status in students at an educational institution in Huanuco - Rodríguez de Lombardi, Gladys Liliana (2019)
Objective. To determine the effect of the healthy lunch box on the eating habits and nutritional status of primary school students at the san Vicente de la Barquera educational institution, Huánuco-2018. Methods. A study with pre-experimental design with application of a stimulus in the school lunch box program was carried out, with test before and after in a single group in 179 students of the primary level; using an interview guide in the collection of the data and a registration form for the nutritional state. The chi-square test of independence was used in the inferential analysis with a statistical significance p < 0.05. Results. In the eating habits variable, after the intervention, the significance value was p < 0.000with changes in 25.1 %, in the nutritional status variable, after the intervention, the significance value was p = 0.026, with changes in 14.5 % in the primary level students under study. Consequently, null hypothesis is rejected and the research hypothesisthat the school lunch box program has a positive effect on the eating habits and nutritional status in the study sample is accepted. Conclusions. The school lunch box program has a positive effect on the eating habits and nutritional status of primary school students at the San Vicente de la Barquera educational institution.